Two-dimensional layered nickel-based coordination polymer for supercapacitive performance. Issue 12 (30th May 2022) - Deka, Rakesh; Kumar, Viresh; Rajak, Richa; Mobin, Shaikh M.
Abstract : A nickel based coordination polymer (Ni-CP ) is synthesized by slow diffusion technique which reveals a 2D layer like structure having sql topology, further this Ni-CP was employed for high performance supercapacitor application. Abstract : Room temperature assisted nickel-coordination polymer (Ni-CP ) is obtained by utilizing the slow diffusion method. The formation of Ni-CP has been confirmed using single-crystal X-ray diffraction (SC-XRD). Ni-CP established a 2D layer structure with average length to diameter ( l /d) ratio of ∼4.19. The binder and additive-free Ni-CP exhibited outstanding pseudocapacitor behavior with a specific capacitance of 802 F g −1 (64 mA h g −1 ) at 3 A g −1 by retaining ∼95% of the initial capacitance over 5000 cycles. For a comparative study, different electrolytic cations (Na +, K +, Li + ) were employed to reveal the diffusion kinetics of Ni-CP . Furthermore, an asymmetric supercapacitor (ASC) device was assembled using Ni-CP as the positive and carbon black (CB) as the negative electrode, respectively. The as-fabricated ASC device displayed an energy density of 15 Wh kg −1 .